Rebalancing Bosnia and Herzegovina : A Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2015)
Twenty years after the end of the war, Bosnia and Herzegovina (BiH) has yet to achieve shared prosperity for its citizens and approach European living standards. The country has been at peace since the end of 1995, but its development model needs adjustment if it is to join the ranks of prosperous European economies. BiH has a disproportionately large public sector that dates back to Yugoslav times and has only been partly reformed since, and the constitutional arrangements under the Dayton and Washington Agreements had as their aim the cessation of war rather than the explicit goal of building a viable and efficient state. Financial inflows, particularly aid and remittances, have been fueling consumption-based economic growth. These inflows were important in post-war recovery, and propelled the country back to middle-income status. However, reaching high levels of income, creating prosperity and eliminating poverty will only happen if BiH shifts toward an economic model that builds on international integration, especially with the EU, BiH’s most important trading partner and anchor of institutional reform. BiH needs to rebalance its development model in two fundamental ways in order to succeed. First, it needs to unleash the potential of the private sector while reducing the footprint of the very large public sector. Second, the economy needs to shift from an inward focus driven by local consumption and imports to the potential of international integration through investments and exports. To achieve this country needs more (and larger) companies, vibrant small and medium sized enterprises and a business environment that allows them to grow and expand output, employment, and exports.